Spa Contributes to the Virulence of Type 18 Group A Streptococci - McLellan, Duncan G. J. (American Society for Microbiology, 2001)
Streptococcal protective antigen (Spa) is a newly described surface protein of group A streptococci that was recently shown to evoke protective antibodies (J. B. Dale, E. Y. Chiang, S. Liu, H. S. Courtney, and D. L. Hasty, J. Clin. Investig. 103:1261–1268, 1999). In this study, we have determined the complete sequence of the spa gene from type 18 streptococci. Purified, recombinant Spa protein evoked antibodies that were bactericidal against type 18 streptococci, confirming the presence of protective epitopes. Sera from patients with acute rheumatic fever contained antibodies against recombinant Spa, indicating that the Spa protein is expressed in vivo and is immunogenic in humans. To determine the role of Spa in the virulence of group A streptococci, we created a series of insertional mutants that were (i) Spa negative and M18 positive, (ii) Spa positive and M18 negative, and (iii) Spa negative and M18 negative. The mutants and the parent M18 strain (18-282) were used in assays to determine resistance to phagocytosis, growth in human blood, and mouse virulence. The results show that Spa is a virulence determinant of group A streptococci and that expression of both Spa and M18 is required for optimal virulence of type 18 streptococci.